Impacto da pandemia de Covid-19 no destreino e contribuição de estratégias de autogestão para um programa de exercício multicomponente na capacidade física, saúde mental e qualidade de vida em pessoas idosas ativas. - Cassemiliano, Gabriela (Universidade Federal de São Carlos, 2025)
Detraining, characterized by the interruption or reduction of training, results in physiological and anatomical losses, and can be either intentional or unintentional. During the Covid-19 pandemic, the interruption of activities and the need for social isolation negatively impacted health, especially among older adults, worsening health variables such as physical capacity, mental health, quality of life, and increasing time spent in sedentary behavior. This context highlighted the need for studies on the effects of detraining and the implementation of interventions to mitigate its consequences in the older adult population. Thus, this thesis was divided into two studies: Study I, entitled “Effects of detraining on physical capacity and its relationship with depressive symptoms, quality of life and sedentary behavior in community-dwelling older adults: a longitudinal study,” was designed to analyze the effects of unintentional detraining caused by the Covid-19 pandemic. Study II, entitled “Effects of a multicomponent exercise program associated with self-management strategies to reduce sedentary behavior in older adults: a single-blind, randomized and controlled clinical trial,” aimed to evaluate the effects of the intervention on variables such as physical capacity, quality of life, mental health, and others, and whether the association with self-management enhanced its effects. Our results allow us to conclude that there was a significant worsening in the variables over the detraining period, especially after 18 months of the pandemic, with these negative effects persisting up to 24 months. However, the intervention based on physical exercise combined with self-management strategies to reduce sedentary behavior promoted significant improvements in physical capacity, functionality, life-space mobility, physical activity levels, and depressive symptoms. Additionally, the intervention was effective in reducing sedentary behavior among community-dwelling older adults, reinforcing the importance of physical exercise, empowering individuals regarding self-care, and providing access to information on how to be physically active and less sedentary.
Impact of the Covid-19 pandemic on detraining and the contribution of self-management strategies in a multicomponent exercise program to physical capacity, mental health, and quality of life in physically active older adults.
Keywords: Destreino; Exercício físico multicomponente; Autogestão; Capacidade física; Saúde mental; Qualidade de vida; Pessoas idosas ativas; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL